The Endogeneity Effects of Conservation Agriculture Adoption on Smallholder Farmers' Food Security Status in Osun State, Nigeria - Olawuyi Seyi Olalekan; Balogun Taofeek Ayodeji (Journal of Economics and Behavioral Studies, 2017)
Goal two of the Sustainable Development Goals stipulates that, individuals at all strata are food secure. This is a major social problem with far reaching economic and development consequences. Growing population has exacerbated the pressure on land base agriculture to supply energy requirements, and traditional agricultural practices have complicated the topical issue. Thus, efforts to simultaneously improve agricultural productivity and keep the system sustainable calls for appropriate sustainable agricultural practice such as conservation agriculture. This study investigates the links between CA adoption and household food security in Nigeria. Two hundred and twenty-one respondents in the study area were sampled. Multisampling technique was used to select the required sample and a questionnaire was administered. Descriptive statistics result revealed farmers’ and farm-based characteristics while food security index divulged the food security status of the respondents. The Double hurdle model was employed to investigate factors driving the adoption of CA and extent of adoption while two-stage least square (2SLS) estimated bi-causal links between CA adoption and food security status. The age of respondents, gender, education, access to credit, farm size cultivated and access to extension services contributed significantly to the adoption of CA and so to the extent of adoption. The two-stage least square confirms the exogeneity of CA adoption with food security status. By implication, the adoption of CA practices in Nigeria is a viable option to increase food production and by extension to attain sustainable food security status.